Evolutionary psychology, economic freedom, trade and benevolence - John D. Levendis; Robert B. Eckhardt; Walter Block (Review of Economic Perspectives, 2019)
Our thesis is that the reason many of us today are inclined toward socialism (explicit cooperation) and against laissez-faire capitalism (implicit cooperation) is because the first type of behavior was much more genetically beneficial during previous generations of our species. There is, however, a seemingly strong argument against this hypothesis: evidence from human prehistory indicates that trade (implicit cooperation) previously was widespread. How, then, can we be hard-wired in favor of socialism and against capitalism if our ancestors were engaged in market behavior in past millennia? Although trade which is self-centered and beneficial (presumably mutually beneficial to all parties in the exchange) did indeed appear hundreds of thousands of years ago, benevolence was established in our hard-wiring very substantially earlier, literally hundreds of millions of years ago, and is therefore far more deeply integrated into the human psyche.
Keywords: Z1; Z10; Z14; 330; Benevolence; capitalism; evolutionary psychology; hard-wiring; profit and loss; selfishness